Tax Extenders Resurrected: Insights on Higher Education Tax Reform from the Recent Legislation on the Tuition and Fees Deduction (Higher Education Politics and Economics, 2020)
U.S. legislators recently brought back thirty-four tax programs from legislative limbo, extending them for three years. This includes the tuition and fee deduction, used by taxpayers to save on college expenses. This regressive tax policy flows heavily towards higher-income levels, with almost a third of the deduction going to those with incomes between $100,000 and $200,000. Previous empirical research indicates the policy has had no effect on increasing college enrollment. It is imperative that researchers, policymakers, and practitioners remediate duplicative, fiscally irresponsible tax policy. To guide this remediation, I provide a legislative history of the tuition and fees deduction, duplicative effects of current education tax incentives, critiques against the current tax extender package, and recommendations for higher education tax reform.